2010
DOI: 10.33549/physiolres.931845
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Effects of Visfatin on Hepatocyte Sensitivity to Insulin Action

Abstract: Visfatin was originally described as an adipokine with insulin mimetic effects. Recently, it was found that visfatin is identical with the Nampt (nicotinamide phosphoribosyltransferase) gene that codes for an intra- and extracellular NAD biosynthetic enzyme and is predominantly expressed outside the adipose tissue. In the current study, we found strong protein and mRNA expression of visfatin in rat heart, liver, kidney, and muscle, while the expression of visfatin in visceral fat was significantly lower and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Besides, researchers have shown that it has an impact on the immune and vascular system (Erfani et al, 2015, Skop et al, 2009. The neuroprotective effect of visfatin was reported by some researchers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Besides, researchers have shown that it has an impact on the immune and vascular system (Erfani et al, 2015, Skop et al, 2009. The neuroprotective effect of visfatin was reported by some researchers.…”
Section: Introductionmentioning
confidence: 94%
“…Fukuhara et al (2005) introduced visfatin as a new adipokine. At first, it was recognized as nicotinamide phosphoribosyltransferase (Nampt) synthetase and then rediscovered as a pre-B cell colony-enhancing factor (PBEF) that induce the formation of pre-B cell colony (Skop et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Visfatin normalized after 6 months of bariatric surgery and consequent weight loss [106]. Visfatin may play an important role in regulating insulin sensitivity in the liver [107]. Visfatin binds to the insulin receptor at a site distinct from insulin and exerts hypoglycemic effect by reducing glucose release from hepatocytes and stimulating glucose utilization in the peripheral tissues [108].…”
Section: Visfatinmentioning
confidence: 99%
“…visfatin actions can be endocrine, paracrine, and autocrine as well. These autocrine effects of visfatin may play an important role in regulating insulin sensitivity in the liver [10]. concentrations of visfatin are increased by hyperglycaemia and lowered HDL-cholesterol level [11], also visfatin plays a pivotal role as regulator of cell energy balance [12].…”
Section: Introductionmentioning
confidence: 99%